The Academic Administration of School Administrators under the Kaewkowit Secondary School Cluster under the Chachoengsao Secondary Educational Service Area Office - เพชรศรี, วิชิต; รักษ์นคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to study, and compare the academic administration of school administrators and study guidelines for developing the academic administration of school administrators under the Kaewkowit secondary school cluster. The sample consisted of 160 teachers in schools within the Kaew Kowit Collaborative Education Zone under the Secondary Educational Service Area Office of Chachoengsao, determined using Krejcie and Morgan's table (1970: 607-610). The research instrument was a 5-level rating scale checklist questionnaire with a reliability of 0.93 and an index of item-objective congruence ranging from 0.80 to 1.00 and Semi-structured Interview. Statistics used included mean, standard deviation, t-test, F-test, and content analysis.          The findings revealed that: 1. The academic administration of school administrators under the Kaewkowit secondary school cluster under the Chachoengsao Secondary Educational Service Area Office was at a high level in all aspects, as follows: curriculum development, teaching management, development and use of educational technology, assessment and evaluation including credit transfer, and educational supervision. 2. The comparing the academic administration of school administrators in the Kaewkowit Secondary School Cluster according to gender, educational level, and work experience, revealed differed with statistical significance at the .05 level. 3. Guidelines for developing the academic administration of school administrators include: administrators should use authentic assessment alongside testing, organize systematic supervision schedules using the true friend model, implement student-centered teaching and learning, promote active learning, develop curricula with evaluation 1-2 times per year to improve content and lesson plans appropriately, develop and use educational technology and media, promote teachers' digital skills, and support the use of AI and new technologies in teaching and learning.